1 - On Student Access and Equity in a Reforming University: Makerere in the 1990s and Beyond - C.Kwesiga, Joy; Ahikire, Josephine (Journal of Higher Education in Africa, 2006)
This paper examines issues of access and equity in the context of the far-ranging reforms that have been taking place at Makerere University and in the Ugandan higher education system generally since the early 1990s. The analysis attempts to map out the contours of student access over time, outlining the major fault lines in student diversities which include, among others, location, class and gender, as well as the state (university) response to these diversities in the context of market based reforms. We argue that key to the reform programme was a reduction in the state’s financial commitment in higher education and the implementation of alternative financial strategies especially relating to the introduction of the private sponsorship programme in 1992. Private sponsorship greatly expanded the intake of fee-paying students, and the total number of students in higher education in Uganda has ex- panded enormously. However, these apparent gains in terms of access to higher education have been offset by lack of necessary investment in facilities, with result- ing problems of over-crowding, excessive teaching loads, large classes and falling standards. The analysis also interrogates the ways in which government/private dynamic plays out in the context of a highly fractured education system, dominated by urban-based schools, particularly located in the south of the country, and how the various affirmative actions measures have in a way, reproduced social and class privilege.